Can nonviolent resistance survive COVID-19?. Issue 3 (27th May 2022) - Chenoweth, Erica
Abstract: When the COVID-19 pandemic arrived on the scene, the near-universal imposition of lockdowns and public health restrictions prompted many human rights advocates to sound the alarm regarding freedoms of assembly, expression, privacy, and movement. Even though they have not yet appeared to reduce the occurrence of protests in many countries, such restrictions may nevertheless diminish the ability of mass movements to effectively organize and win key concessions. In this article, I present new descriptive data on the outcomes of people-power movements, which suggest that, despite their heightened popularity, maximalist nonviolent campaigns are seeing their lowest success rates in more than a century. I describe how the diffusion of restrictions on peaceful assembly and expression accompanies a broader toolkit of authoritarian strategies that have become standardized over the past 15 years in response to people-power movements. I then turn to three tensions that present dilemmas for movements emerging from the pandemic and its associated lockdowns. I conclude by laying out key research questions that emerge from these trends and dilemmas that require sustained attention from scholars and practitioners of nonviolent resistance.